OBSERVATIONS ON SOME ASPECTS OF BIOLOGY OF PENTAPRION LONGIMANUS (CANTOR) - Rao, T Appa (Indian Journal of Fisheries, 2011)
Ehiring the period 1984 -'88, catches and catch per hour values of Pentaprion hngimanus fluctuated fromyear to year and month to month but the annual average catches together with catch rates showedincreasing trend. The spawning period of P. hngimanus is short extending from December to March.Average fecundity was found to be 3,023 eggs and fecundity increased with weight of ovary and to aless extent with the length of fish